Exposing the inside of the fine-grained siliciclastic tidal shelf deposits of the Alicia Formation, Tandilia Basin, during the Ediacaran anoxia in the Clymene Ocean - Arrouy, Maria Julia; Gómez Peral, Lucia (Journal of South American Earth Sciences)
In this contribution we outline the outstanding attributes and inferred depositional controls for dark mudstones of the Alicia Formation (~570 Ma) in order to reveal the intrinsic characteristics of unknown Ediacaran marine depositional conditions into the basin. The Alicia Formation represents a continuous and undeformed ~150 m thick sequence in which nine siliciclastic lithofacies were accumulated controlled by the Clymene sea conditions. Sedimentary facies analysis of their fine-grained rocks reveals a deposition across two depositional sequences. The basal portion is described as formed in an upper offshore while the upper portion represents a lower shoreface environment. This study combines the stratigraphic characterization with detailed facies descriptions, petrography, XRD, SEM and geochemistry analyses. This succession was deposited under relatively constant marine environmental conditions with relative sea level variations manifested between the fair-weather and storm wave bases. Bottom-water conditions during its sedimentation show fluctuations in the geochemical indicators as redox-sensitives (U, Mo, V), terrigenous supply (Si, Al, Zr, Th), carbonate productivity (CaO) and organic productivity (Cu, Ni, P/Al). This research represents an exceptional example of preserved fine-grained Ediacaran tidal shelf deposits in the Tandilia Basin. The data provide evidence for the middle Ediacaran anoxia, which post-dates a previous oceanic oxygenation event (EOO, 580 Ma) and pre-dates the white sea assemblage radiation (560 Ma) probably developed in a well oxygenated sea. Within the SW Gondwana scenario, our findings may support a link between the depositional setting during most severe redox changes. Fil: Arrouy, Maria Julia. Universidad Nacional del Centro de la Provincia de Buenos Aires. Rectorado. Instituto de Hidrología de Llanuras - Sede Azul. Provincia de Buenos Aires. Gobernación. Comisión de Investigaciones Científicas. Instituto de Hidrología de Llanuras - Sede Azul; Argentina. Consejo Nacional de ...